Syntheis of unusual tricyclic ring systems of biological interest - Mohapatra, Debendra K.; Maity, Pradip K.; Chorghade, Mukund S.; Gurjar, Mukund K. (Heterocycles, 2007)
We describe a new synthesis of tricyclic scaffolds that incorporate a fusion of triazole with 1,4-benzodiazepine utilizing intramolecular ``click'' chemistry.
Keywords: 1; 2; 3-Triazole; 4-benzodiazepine; Click chemistry; nitrogen rich polycyclic hetero-system; privileged structure